Faktor - Faktor Yang Mempengaruhi Biaya Utang Pada Perusahaan Dalam KOMPAS 100 - Muhamad Septian; Rosinta Ria Panggabean (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
This study aims to determine the effect of Good Corporate Governance (GCG) which is proxied through the proportion of independent commissioners, managerial ownership, institutional ownership, quality audits, and family ownership on the cost of debt. The objects of this study are companies listed in Compass 100 period August 2013 January 2014. The method used to take samples of the study using the purposive sampling method. Data analysis methods used are descriptive statistics, the classical assumption test, and the hypotheses test. Based on the results of hypothesis testing that was performed by using multiple regression analysis at the 0.05 significant level, the results of this study prove that the proportion of independent commissioners has a significant negative effect on the cost of debt. Managerial ownership has a positive significant effect on the cost of debt. Institutional ownership, quality audits, and family ownership have no significant effect on the cost of debt.